2001
DOI: 10.4049/jimmunol.166.1.574
|View full text |Cite
|
Sign up to set email alerts
|

CD11b/CD18 Acts in Concert with CD14 and Toll-Like Receptor (TLR) 4 to Elicit Full Lipopolysaccharide and Taxol-Inducible Gene Expression

Abstract: Overproduction of inflammatory mediators by macrophages in response to Gram-negative LPS has been implicated in septic shock. Recent reports indicate that three membrane-associated proteins, CD14, CD11b/CD18, and Toll-like receptor (TLR) 4, may serve as LPS recognition and/or signaling receptors in murine macrophages. Therefore, the relative contribution of these proteins in the induction of cyclooxygenase 2 (COX-2), IL-12 p35, IL-12 p40, TNF-α, IFN-inducible protein (IP)-10, and IFN consensus sequence binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
285
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 371 publications
(310 citation statements)
references
References 68 publications
19
285
0
4
Order By: Relevance
“…At pharmacologically low concentrations (exemplified by 1 mM in this study), the JNK signaling pathway was the major stimulator of IL-6 gene regulation. However, at suprapharmacologically high concentrations (exemplified by 50 mM in this study), paclitaxel exerted LPS-like effects likely through the TLR4 signaling pathway as reported previously (Kawasaki et al, 2000(Kawasaki et al, , 2003Perera et al, 2001). Elucidation of the signaling networks that are differentially initiated by low concentrations or by high concentrations of paclitaxel and the verification of specific inhibitors against key molecules inside the networks may help us in developing a better chemotherapeutic strategy in treatment of ovarian cancer with paclitaxel.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…At pharmacologically low concentrations (exemplified by 1 mM in this study), the JNK signaling pathway was the major stimulator of IL-6 gene regulation. However, at suprapharmacologically high concentrations (exemplified by 50 mM in this study), paclitaxel exerted LPS-like effects likely through the TLR4 signaling pathway as reported previously (Kawasaki et al, 2000(Kawasaki et al, , 2003Perera et al, 2001). Elucidation of the signaling networks that are differentially initiated by low concentrations or by high concentrations of paclitaxel and the verification of specific inhibitors against key molecules inside the networks may help us in developing a better chemotherapeutic strategy in treatment of ovarian cancer with paclitaxel.…”
Section: Discussionsupporting
confidence: 71%
“…Taken together, these results indicated that two pathways ( Figure 7) are involved in the upregulation of IL-6 by treatment with paclitaxel: (a) at low, pharmacological concentrations (exemplified by 1 mM in this study), the JNK signaling pathway was the major stimulator of IL-6 gene regulation, and (b) at high, suprapharmacological concentrations (exemplified by 50 mM in this study), paclitaxel exerted LPS-like effects, which were most likely carried out through the TLR4 signaling pathway as reported previously (Kawasaki et al, 2000(Kawasaki et al, , 2003Perera et al, 2001). …”
Section: Sp600125supporting
confidence: 74%
See 3 more Smart Citations